Energy Efficiency Analysis of Trawlers (Case Study: Indonesian’s Trawler) - Dasira, Alyuan; Laurens, Jean Marc (Institut Teknologi Sepuluh Nopember, 2014)
Nowadays, the energy efficiency is of most importance in all economical activities. For the fishing industry, it is particularly critical. Energy efficiency in the fishing sector can be expressed in term of the ratio of fishing capture over operational cost. The fuel cost in ship operation became a dominant factor of the total operational cost. Moreover, fuel cost is high and continues to increase. One way to achieve better energy efficiency is to use a high efficiency ship propeller in order to diminish fuel consumption. Trawlers have two main operational conditions; they are the voyage condition and the trawling condition. The voyage condition is when the trawler travels to port and to the fishing grounds. The trawling condition is when the trawler pulls the trawl to catch fish. Most of trawler problem is in trawling operation with trawls, the ship resistance increased tremendously and then the propeller must work harder to ensure the ship can advance against the trawling resistance at low speed, 3, 5 Knots. This condition corresponds to a heavy load condition. In this condition, the propeller efficiency is low. Duct propeller is one of the configurations that increase the propeller efficiency in heavy loaded condition. The other strategy is to increase the energy efficiency is to optimize ship speed in voyage condition. In this research, the numerical simulations performed for the propeller-duct interactions were made possible thank to an iterative procedure where the flow around each of the several components are modeled with a potential flow theory. Boundary element Method (BEM) or panel method is used to solve the potential flow model. The models and methods are described in the document as well as the iterative procedure that has been developed within the framework of this project. We have investigated energy efficiency with fuel consumption approach. Propeller with and without duct in same size (B3-65 and Kaplan 65 in Duct 19A) are analyzed and optimized ship speed 9 Knots to 7 Knots. It shows that 13.7 % of the fuel consumption was saved with a duct propeller in trawling condition and 35% of the fuel consumption was saved with an optimized ship speed in voyage condition.